THE ROLE OF TEACHER LEADERS IN ORGANIZING AND CREATING ENVIRONMENTALLY FRIENDLY SCHOOLS: THE PATH TO SUSTAINABLE DEVELOPMENT (EDUCATION IN THE 21ST CENTURY, 2025)
Eco-schools or green schools are not only aimed at protecting the environment, but also contribute to the formation of an educational environment in which students and teachers work together to develop strategies that link social justice, solving environmental problems and economic stability. The importance of environmental education in these schools is inevitably linked to an ecological society, as well as social factors that contribute to the improvement of public relations and progress in transformation.The work explores the role of environmental schools and environmental education in sustainable development education, focusing on the importance of teacher leadership. The article presents the basic principles of eco-schools, their structural models and their impact on․
Keywords: Eco-schools; green education; sustainable development; environmental education; teacher leadership; community participation; educational policy; social justice; environmental awareness